UNDERSTANDING CLOUD SECURITY POSTURE MANAGEMENT (CSPM): A COMPREHENSIVE GUIDE - Vishnuvardhana Reddy Veeraballi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Cloud Security Posture Management (CSPM) has emerged as a critical component in modern cloud security architecture, offering organizations comprehensive solutions for protecting their cloud infrastructure. This technical article explores the fundamental aspects of CSPM, including its core components, implementation strategies, security benefits, and future trends. The article examines how CSPM solutions enable automated security monitoring, compliance management, and risk assessment across diverse cloud environments. Through integration with existing security tools and frameworks, CSPM platforms provide organizations with enhanced visibility, control, and operational efficiency while addressing the growing challenges of cloud security management.